Fatigue crack initiation in AA2024: A coupled micromechanical testing and crystal plasticity study. Issue 1 (17th September 2018) - Efthymiadis, Panos; Pinna, Christophe; Yates, John R.
Abstract: A new combined experimental and modelling approach has been developed in order to understand the physical mechanisms that lead to crack nucleation in a polycrystalline aluminium alloy AA2024 undergoing cyclic loading. Four‐point bending low‐cycle fatigue tests were performed inside the chamber of a scanning electron microscope on specimens with a through‐thickness central hole, introduced to localize stresses and strains in a small region on the top surface of the sample. Fatigue crack initiation and small crack growth mechanisms were analyzed through high‐resolution scanning electron microscope images, local orientation measurements using electron‐back‐scattered‐diffraction, and local strain measurements using digital image correlation. A crystal plasticity finite element model was developed to simulate the cyclic deformation behaviour of AA2024. Two‐dimensional Voronoi‐based microstructures were generated, and the material parameters for the constitutive equations (including both isotropic and kinematic hardening) were identified using monotonic and fully reversed cyclic tests. A commonly used fatigue crack initiation criterion found in the literature, the maximum accumulated plastic slip, was evaluated in the crystal plasticity finite element model but could not predict the formation of cracks away from the edge of the hole in the deformed specimens. A new criterion combining 2 parameters: The maximum accumulated slip over each individual (critical) slip system and the maximum accumulated slip over all slip systems were formulated to reproduce the experimental locations of crack nucleation in the microstructure.